1975
DOI: 10.1172/jci108038
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal control of ketogenesis. Rapid activation of hepatic ketogenic capacity in fed rats by anti-insulin serum and glucagon.

Abstract: A B STR A CT The enhanced capacity for long-chain fatty acid oxidation and ketogenesis that develops in the rat liver between 6 and 9 h after the onset of starvation was shown to be inducible much more rapidly by administration of anti-insulin serum or glucagon to fed rats. After only 1 h of treatment with either agent, the liver had clearly switched from a "nonketogenic" to a "ketogenic" profile, as determined by rates of acetoacetate and 1-hydroxybutyrate production on perfusion with oleic acid. As was the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(77 citation statements)
references
References 38 publications
8
68
1
Order By: Relevance
“…3. The objective here was to treat fasted rats with NA, but to maintain a high plasma FFA level by coinfusion of a triglyceride emulsion (Intralipid) plus heparin, a well established maneuver that promotes intravascular lipolysis (21). In the three groups of animals depicted, the starting ( Ϫ 60 min) plasma FFA concentration ranged from ‫ف‬ 1.2-1.5 mM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3. The objective here was to treat fasted rats with NA, but to maintain a high plasma FFA level by coinfusion of a triglyceride emulsion (Intralipid) plus heparin, a well established maneuver that promotes intravascular lipolysis (21). In the three groups of animals depicted, the starting ( Ϫ 60 min) plasma FFA concentration ranged from ‫ف‬ 1.2-1.5 mM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, several in vitro studies have shown that glucagon can enhance hepatic ketone body production directly (41,49). In the rat in vivo, McGarry and co-workers (50) have demonstrated that physiologic quantities of glucagon can convert the fed liver to a ketogenic mode. Possibly, a similar key action of glucagon in the human liver could explain, in part, the lack of ketoacidosis after withdrawal of insulin from ketosis-prone diabetics during suppression of glucagon secretion (33).…”
Section: Discussionmentioning
confidence: 99%
“…The peak in hepatic carnitine soon after birth indicated that the rise was most likely a postnatal rather than an antenatal event. This increase coincides with a greater functional capacity to oxidize fatty acids and produce ketones (4,27). The amount of hepatic carnitine is not rate limiting for fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of hepatic carnitine is not rate limiting for fatty acid oxidation. However, the striking increase in carnitine constitutes an indicator, and a possible promoter, of the heightened fatty acid oxidation in newborns (4,(27)(28)(29). The postnatal fall in carnitine was due to decreasing SCAC esters in piglets, whereas that in rodents was due to a decline in the free fraction (4).…”
Section: Discussionmentioning
confidence: 99%